2015
DOI: 10.1007/s12078-015-9175-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Sensory and Nephelometric Evaluations of Tannin Fractions Obtained by Ultrafiltration of Red Wines

Abstract: Introduction: Although the assessment of red wine quality relies primarily on a sensory description of tannins, it may be usefully completed by some knowledge of the physicochemical properties of these tannins. The present study has a double aim: (1) to gain insight into the sensory properties of subpopulations of proanthocyanidic tannins of different molecular sizes (obtained through several ultrafiltration steps), as well as into the kinetics of the haze formed by these fractions when reacted with polyvinylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Wine tannins consist essentially of proanthocyanidins (condensed tannins) made by polymerization of 3flavanyl monomers (catechins and gallocatechins, epicatechins and epigallocatechins and their galloylated forms) in which two main classes are procyanidins and prodelphinidins (Porter et al, 1985). It was found that they are the major contributors to the body and mouth feel (astringency) of wine (Rébénaque et al, 2015), as well as color stabilizers of wine by forming long-lived polymeric complexes with anthocyanins (Ribéreau-Gayon et al, 2006).…”
Section: Polyphenolic Profile Of Winesmentioning
confidence: 99%
“…Wine tannins consist essentially of proanthocyanidins (condensed tannins) made by polymerization of 3flavanyl monomers (catechins and gallocatechins, epicatechins and epigallocatechins and their galloylated forms) in which two main classes are procyanidins and prodelphinidins (Porter et al, 1985). It was found that they are the major contributors to the body and mouth feel (astringency) of wine (Rébénaque et al, 2015), as well as color stabilizers of wine by forming long-lived polymeric complexes with anthocyanins (Ribéreau-Gayon et al, 2006).…”
Section: Polyphenolic Profile Of Winesmentioning
confidence: 99%
“…Based on polyphenol/mucin reactivity, a micro-plate assay was also developed [151]. Tannic acid [150], grape seed extracts [151], wine extracts [63], tannin fractions added to model solutions [152] were analysed by nephelometry. The turbidity of the solution, formed by the tannin-protein aggregates, linearly correlated with astringency.…”
Section: Nephelometry: Pros and Contrasmentioning
confidence: 99%